SME competitiveness and internationalization field lab internationalization plan for Weshare - Hartmann, Max Phillip (2022)
This work project aims to develop an internationalization strategy for We Share following an IMS process and to identify the most suitable European market. The methodology is twofold: First, relevant literature on the topic of IMS was reviewed. Second, the literature was complemented with findings from interviews ,strategic analysis, as well as a country ranking and cluster analysis. The findings revealed France to be the most attractive market for We Share to expand to with Paris as the first city to operate in. The work, however, contains various limitations and thus, leaves room for a more in-depth analysis.